Analisis Sensitivitas pada Pipa Besi Cor Dengan Retakan Kearah Melingkar Pipa - Gunawan (Universitas Sriwijaya, 2009)
Effect of pressure in the pipe at the rate of leakage from the pipe which is one of the main factors affecting the leak still not adequately understood. In this study conducted in the case of uni-axial stress and bi-axial with finite element method to pipe with a circumferential cracks. Flow rate of crack calculated by the equation torricolli. Exponential component crack for uni-axial tension will decrease if the crack length increases. While the bi-axial pressure, the opposite occurred. So that cracks will tend to open when the crack length increases and the crack length direction of the circular will have more surface area to open the cracks. Keywords : pipe, circumferential, crack